Preschool Nutrition and Subsequent Schooling Attainment: Longitudinal Evidence from Tanzania - Alderman, Harold; Hoogeveen, Hans; Rossi, Mariacristina (2012)
This study analyzes how childhood health determines future academic performance in the Kagera region in Tanzania. Academic outcomes considered are years of education and delay in enrollment, and the measure of childhood health is height (relative to the median). The repercussions of malnutrition in childhood on subsequent learning and school performance are analyzed by using a unique longitudinal data set. Results indicate the degree to which malnutrition leads to reduced lifetime earning capacity due to both delays in schooling and declines in total schooling.